Programming nonreciprocity and reversibility in multistable mechanical metamaterials - Gabriele Librandi (Nature Portfolio, 2021)
This work presents a mechanical metamaterial with 1D array of bistable arches where nonreciprocity and reversibility can be independently programmed. The effects of asymmetry both at the structural and element level on propagation of transition waves are examined.